Práticas colaborativas e ensino da Arquitetura. A experiência dos Laboratórios de Intervenção em Arquitetura in situ/ - Ramalhete, F.; Lages, J.; Silva, S.; Caldas, J. C. (Espaços Vividos e Espaços Construídos, 2019)
This paper presents the project Laboratory of Intervention in Architecture in situ/, started in 2012 and already with seven editions. It is a project of intervention in the community, promoted by CEACT/UAL – Centro de Estudos de Arquitetura, Cidade e Território da Universidade Autónoma de Lisboa, in collaboration with the Municipality of Almada and several local institutions. The article presents a critical analysis of traditional planning, and of alternative interventions to it, which discuss the agents' ability to intervene and in influence the traditional system, questioning its ability to integrate approaches that point out new solutions to old problems. Thse type of intervention were conceptualized as a community of practice within a context of spatial agency, allowing us to observe recent experiences as initiatives to respond to the problems that traditional planning, despite its virtues, has not been able to solve. Through the case study presented, it is argued that it is necessary to values actors with spatial agency capacity in these processes, as they promote an active intervention that drives to long-term changes.